Comparative Analysis of Virulence and Toxin Expression of Vancomycin-Intermediate and Vancomycin-Sensitive Staphylococcus aureus Strains - Jin, Ye; Yu, Xiao; Zhang, Shuntian; Kong, Xiaoyang; Chen, Weiwei; Luo, Qixia; Zheng, Beiwen; Xiao, Yonghong (Frontiers in Microbiology, 2020)
Previous studies on vancomycin-intermediate Staphylococcus aureus (VISA) have mainly focused on drug resistance, the evolution of differences in virulence between VISA and vancomycin-sensitive S. aureus (VSSA) requires further investigation. To address this issue, in this study, we compared the virulence and toxin profiles of pair groups of VISA and VSSA strains, including a series of vancomycin-resistant induced S. aureus strains—SA0534, SA0534-V8, and SA0534-V16. We established a mouse skin infection model to evaluate the invasive capacity of VISA strains, and found that although mice infected with VISA had smaller-sized abscesses than those infected with VSSA, the abscesses persisted for a longer period (up to 9 days). Infection with VISA strains was associated with a lower mortality rate in Galleria mellonella larvae compared to infection with VSSA strains (≥ 40% vs. ≤ 3% survival at 28 h). Additionally, VISA were more effective in colonizing the nasal passage of mice than VSSA, and in vitro experiments showed that while VISA strains were less virulent they showed enhanced intracellular survival compared to VSSA strains. RNA sequencing of VISA strains revealed significant differences in the expression levels of the agr, hla, cap, spa, clfB, and sbi genes and suggested that platelet activation is only weakly induced by VISA. Collectively, our findings indicate that VISA is less virulent than VSSA but has a greater capacity to colonize human hosts and evade destruction by the host innate immune system, resulting in persistent and chronic S. aureus infection.